2021
DOI: 10.3390/ijms221910853
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal Mechanism of Isoxanthohumol from Humulus lupulus Linn.

Abstract: Humulus lupulus Linn. is a traditional medicinal and edible plant with several biological properties. The aims of this work were: (1) to evaluate the in vitro antifungal activity of H. lupulus ethanolic extract; (2) to study the in vitro and in vivo antifungal activity of isoxanthohumol, an isoprene flavonoid from H. lupulus, against Botrytis cinerea; and (3) to explore the antifungal mechanism of isoxanthohumol on B. cinerea. The present data revealed that the ethanolic extract of H. lupulus exhibited moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Petri dishes were incubated at 25°C, and the mycelial growth diameter was measured using the cross-bracketing method until the fungal growth of the blank control had completely covered the Petri dishes. The inhibitory rates were calculated according to the following formula (Yan et al, 2021 ):…”
Section: Methodsmentioning
confidence: 99%
“…Petri dishes were incubated at 25°C, and the mycelial growth diameter was measured using the cross-bracketing method until the fungal growth of the blank control had completely covered the Petri dishes. The inhibitory rates were calculated according to the following formula (Yan et al, 2021 ):…”
Section: Methodsmentioning
confidence: 99%
“…Their role in plants seems to be poorly documented, while their estrogenic activities, which are essentially provided by 8-prenylnaringenin, are often cited. However, Yan et al, [ 23 ] recently reported a significant anti-fungal activity of isoxanthohumol on Botritis cinerea . This means that the prenylflavanones can act as phytoalexins in hops.…”
Section: Definition and Originmentioning
confidence: 99%
“…Ethanolic extract of Humulus lupulus containing isoxanthohumol exhibited moderate antifungal activity against five tested phytopathogenic fungi in vitro but proved highly efficient in vivo against Botrytis cinerea , a broad range plant pathogen. Interestingly, the antifungal mechanism was connected to the carbohydrate metabolic process: The TCA cycle as well as respiration were inhibited upon exposure to isoxanthohumol, consequently preventing ATP production [ 72 ]. Consequently, membrane lipid peroxidation occurred together with an increased expression of redox enzymes, including SOD, catalase, APX, and GPX, and of H 2 O 2 concentration.…”
Section: Targeting the Fungal Tca Cycle To Perturb The Redox Balancementioning
confidence: 99%